Respostas

2012-12-29T13:16:24-02:00
(x+1)!=3 (x!)

 x! + 1!= 3x!

 x!- 3x!= -1

-2x! = -1 .(-1)

 2x!= 1

 x= 1/2!

 

Pronto, é isso!!

4 3 4
  • Usuário do Brainly
2012-12-29T15:10:52-02:00

(x + 1)! = 3x!

Definindo fatorial:

        n! = n.(n - 1).(n - 2).(n - 3).......(n - n + 1)!

 

Logo:

        (x + 1)! = (x + 1). (x + 1 - 1)! = (x +1).x! = 3x!

        De onde, dividindo ambososmenbros por x!:

                                                           (x + 1) = 3

                                                                    x = 2

 

                                                            Comprobação:

                                                                     (2 + 1)! = 3.(2 + 1 - 1) = 3.2.1 = 6 = 3x! = 6

                                                                                                                            6 = 6 

                                                                                                   

3 4 3